<span>y = <span>x2 </span>+ 5x + 36
y = (<span>x2 </span>− 5x − 36)</span>
<span>y = (<span>x2 </span>− 9x + 4x − 36)</span>
<span>y = [x (x − 9) + 4 (x − 9)]</span>
<span>y = (x − 9)(x + 4)</span>
The function is:
f ( x ) = 2 / ( x² + 3 x - 10 )
x² + 3 x - 10 = x² + 5 x - 2 x - 10 = x ( x + 5 ) - 2 ( x + 5 ) =
= ( x + 5 ) ( x - 2 )
x + 5 = 0 => x = - 5
x - 2 = 0 => x = 2
Answer:
The vertical asymptotes are: x = - 5 and x = 2.
2+ 0.0+ 0.05+ 0.009okay so you just have to add the numbers. so you add 2+0.0+0.5+0.009. then you will get you answer. i hope this helps!!!!
Answer:
r = 8°
Step-by-step explanation:
95° = 6r° + 47° ( vertically opposite angles are equal)
6r° = 95° - 47°
6r = 48°
r = 48°/6
r = 8°